An Analytical Approach to the Unified Solution of Kinetic Equations in Rarefied Gas Dynamics. I. Flow Problems - C. S. Scherer, J. F. Prolo Filho; Barichello, L.B. (Zeitschrift für Angewandte Mathematik und Physik, 2009)
n/a
n/a